2016
DOI: 10.1055/s-0042-105557
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between endoscopic mucosal resection and hot snare resection of large nonpedunculated colorectal polyps: a randomized trial

Abstract: EMR and hot snare resection appear to achieve similar complete resection rates for polyps up to 14 mm; however, EMR may be superior for larger polyps, particularly for those ≥ 20 mm.Registered at Clinicaltrials.gov: NCT 01950117.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…68 Our study indicates that expert endoscopists have lower IRRs compared with multi-endoscopist studies. 28,31,32,39,[46][47][48] We found no statistically significant difference for IRRs when submucosal injections were performed for polyps 10 mm. This technique might prove more beneficial for 10-to 20-mm polyps; however, there is a lack of studies performed in that population without submucosal injections.…”
Section: Discussionmentioning
confidence: 51%
“…68 Our study indicates that expert endoscopists have lower IRRs compared with multi-endoscopist studies. 28,31,32,39,[46][47][48] We found no statistically significant difference for IRRs when submucosal injections were performed for polyps 10 mm. This technique might prove more beneficial for 10-to 20-mm polyps; however, there is a lack of studies performed in that population without submucosal injections.…”
Section: Discussionmentioning
confidence: 51%
“…[3][4][5] The reported risk of incomplete resection varies between 2% and 20% depending on resection technique and polyp histology. [3][4][5][6][7] In the complete adenoma resection study (CARE), the incomplete resection of 10-to 20-mm neoplastic polyps was 17%. 4 However, the natural history of residual polyp tissue is not known, and it remains unclear how important minute residual polyp tissue is and whether it may regrow.…”
Section: Discussionmentioning
confidence: 99%
“…R0 resection rates using CSP for diminutive and small colorectal polyps range from 53 to 98% [16][17][18][19][20]. R0 resection rates for alternative techniques, HSP and EMR are also available and are similar to CSP, likely reflecting appropriate selection of polypectomy technique based on polyp morphology [19,21] (Table 1).…”
Section: Residual Adenoma/dysplastic Tissuementioning
confidence: 99%
“…A polyp size of >15 mm was four times more likely to be incompletely resected. R0 resections by EMR were reported in 90% of polyps <19 mm versus 75% for those 20 mm and larger [21]. Several of these studies have also found sessile serrated polyp (SSP) compared to standard adenoma histology to be a risk factor for residual disease as assessed by margin EMR and biopsy, with odds ratios of 2.8 and 3.4, respectively [25,30,31].…”
Section: Risk Factors For Incomplete Polypectomymentioning
confidence: 99%